Design and Validation of Isomorphic Crystal Library for Nonlinear Optics and THz Wave Generation - Shin, Bong Rim; Yu, In Cheol; Puc, Uros; Kim, Won Tae; Yoon, Woojin; Kim, Chaeyoon; Yun, Hoseop; Kim, Dongwook; Jazbinsek, Mojca; Rotermund, Fabian; Kwon, O. Pil (Advanced Optical Materials, 2023)
Development of new organic crystals possessing large second-order optical nonlinearity is very challenging because of strong tendency of centrosymmetric dipole–dipole molecular assembly in crystals. This tendency makes it difficult to develop various analogous crystals that allow fine tuning of optical and physical properties to enhance the device performance. A design approach of an isomorphic crystal library consisting of 11 highly efficient nonlinear optical salt crystals is reported. Analyzing the so-called isomorphic tolerance space in previously reported mother crystals (PMnXQ chromophores, where PM denotes piperidin-4-ylmethanol electron donor, n corresponds to the substituted position of halogen (X) group on the quinolinium (Q) electron acceptor), various substituents are introduced into the PMnXQ crystals at different positions, considering their space-filling characteristics and interionic interaction ability. All 11 PMnXQ crystals exhibit an isomorphic (or pseudo-isomorphic) crystal structure, in which the cationic chromophores form a perfectly parallel assembly for maximizing the second-order nonlinear optical susceptibility. The optical, physical, and crystal characteristics of newly designed, synthesized, and grown isomorphic PMnXQ crystals show both similarities and differences. Excellent THz wave-generation performance is demonstrated in both kHz- and MHz-repetition optical pump systems with new PMnXQ crystals. Therefore, the design approach using isomorphic tolerance space is very attractive for developing diverse isomorphic analogous organic crystals.
Keywords: Centrosymmetric; Crystal possessing; Design approaches; Dipole-dipole; Molecular assembly; Organic crystal; Second order optical nonlinearity; THz waves; Tolerance spaces; Wave generation; nonlinear optics; organic crystals; terahertz waves